Let $P,Q,R$ be defined as
\[\begin{align}
& P={{a}^{2}}b+a{{b}^{2}}-{{a}^{2}}c-a{{c}^{2}} \\
& Q={{b}^{2}}c+b{{c}^{2}}-{{a}^{2}}b-a{{b}^{2}} \\
& R={{c}^{2}}a+c{{a}^{2}}-{{c}^{2}}b-c{{b}^{2}} \\
\end{align}\]
where $a,b,c$ are all $+ive$ and the equation $P{{x}^{2}}+Qx+R=0$ has equal roots then $a,b,c$ are in \[\]
A. A.P. \[\]
B. G.P.\[\]
C. H.P.\[\]
D. None of these\[\]
Answer
Verified
457.2k+ views
Hint: We take ${{a}^{2}},a$ common in $P$, ${{b}^{2}},b$ common in $Q$ and ${{c}^{2}},c$ common in $R$ to express $P,Q,R$ in cyclical form. We put the cyclical expression of $P,Q,R$ in $P{{x}^{2}}+Qx+R=0$ and using the given condition equate the discriminant to zero. We simplify the discriminant equation until we get a relation only in $a,b,c$. If the relation is $2b=a+c$ then $a,b,c$ are in arithmetic progression (AP), if the relation is ${{b}^{2}}=ac$ then $a,b,c$ are in geometric progression (GP) and if the relation is $\dfrac{1}{a}+\dfrac{1}{c}=\dfrac{2}{b}$ then $a,b,c$ are in harmonic progression (HP).\[\]
Complete step-by-step answer:
We know that the standard quadratic equation is given by $a{{x}^{2}}+bx+c=0$ where $a,b,c$ are real numbers with condition has equal roots when the discriminant $D$ satisfies the condition $D={{b}^{2}}-4ac=0$
We are given from the question three expressions of $P,Q,R$ respectively as
\[\begin{align}
& P={{a}^{2}}b+a{{b}^{2}}-{{a}^{2}}c-a{{c}^{2}} \\
& Q={{b}^{2}}c+b{{c}^{2}}-{{a}^{2}}b-a{{b}^{2}} \\
& R={{c}^{2}}a+c{{a}^{2}}-{{c}^{2}}b-c{{b}^{2}} \\
\end{align}\]
We try to express $P,Q,R$ in cyclical form by taking ${{a}^{2}},a$ common in $P$, ${{b}^{2}},b$ common in $Q$ and ${{c}^{2}},c$ common in $R$. We have,
\[\begin{align}
& P={{a}^{2}}\left( b-c \right)+a\left( {{b}^{2}}-{{c}^{2}} \right)={{a}^{2}}\left( b-c \right)+a\left( b-c \right)\left( b+c \right)=a\left( b-c \right)\left( a+b+c \right) \\
& Q={{b}^{2}}\left( c-a \right)+b\left( {{c}^{2}}-{{a}^{2}} \right)={{b}^{2}}\left( c-a \right)+b\left( c-a \right)\left( c+a \right)=b\left( c-a \right)\left( a+b+c \right) \\
& R={{c}^{2}}\left( a-b \right)+c\left( {{a}^{2}}-{{b}^{2}} \right)={{c}^{2}}\left( a-b \right)+c\left( a-b \right)\left( a+b \right)=c\left( a-b \right)\left( a+b+c \right) \\
\end{align}\]
We are further given in the question that $a,b,c$ are all positive real numbers and the equation $P{{x}^{2}}+Qx+R=0$ has equal roots. We can put the value of $P,Q,R$ in the given quadratic equation $P{{x}^{2}}+Qx+R=0$ and have,
\[\Rightarrow a\left( b-c \right)\left( a+b+c \right){{x}^{2}}+b\left( c-a \right)\left( a+b+c \right)x+c\left( a-b \right)\left( a+b+c \right)=0\]
Since $a,b,c$ are positive real numbers $a+b+c$ cannot be zero and we can divide $a+b+c$ in both side of the above equation to have,
\[\Rightarrow a\left( b-c \right){{x}^{2}}+b\left( c-a \right)x+c\left( a-b \right)=0\]
The discriminant of the above quadratic equation is zero since the quadratic equation has equal roots. So we have
\[\begin{align}
& {{\left( b\left( c-a \right) \right)}^{2}}-4\times a\left( b-c \right)\times c\times \left( a-b \right)=0 \\
& \Rightarrow {{b}^{2}}{{\left( c-a \right)}^{2}}-4ac\left( ab-{{b}^{2}}-ca+bc \right)=0 \\
& \Rightarrow {{b}^{2}}{{c}^{2}}+{{b}^{2}}{{a}^{2}}-2a{{b}^{2}}c-4{{a}^{2}}bc+4a{{b}^{2}}c+4{{a}^{2}}{{c}^{2}}-4ab{{c}^{2}}=0 \\
& \Rightarrow {{a}^{2}}{{b}^{2}}+{{b}^{2}}{{c}^{2}}+4{{a}^{2}}{{c}^{2}}+2a{{b}^{2}}c-4ab{{c}^{2}}-4{{a}^{2}}bc=0 \\
& \Rightarrow {{\left( ab \right)}^{2}}+{{\left( bc \right)}^{2}}+{{\left( -2ac \right)}^{2}}+2\times ab\times bc+2\times bc\times \left( -2ac \right)+2\times ab\times \left( -2ac \right)=0 \\
\end{align}\]
We use the algebraic identity ${{\left( x+y+z \right)}^{2}}={{x}^{2}}+{{y}^{2}}+{{z}^{2}}+2xy+2yz+2zx$ for $x=ab,y=bc,z=-2ac$ in the above step to have
\[\Rightarrow {{\left( ab+bc-2ac \right)}^{2}}=0\]
We take square root of both side of the above step to have,
\[\begin{align}
& \Rightarrow ab+bc-2ac=0 \\
& \Rightarrow ab+bc=2ac \\
\end{align}\]
Since $a,b,c$ are positive real numbers $abc$ cannot be zero and we can divide $abc$ in both side of the above equation to have,
\[\Rightarrow \dfrac{1}{a}+\dfrac{1}{c}=\dfrac{2}{b}\]
The above relation implies that $a,b,c$ are in HP. So the correct option C\[\]
So, the correct answer is “Option C”.
Note: We can alternatively solve using the product of roots of $P{{x}^{2}}+Qx+R=0$ and equating it to a constant. The key in this problem is to express the discriminant into a square of $\left( ab+bc-2ac \right)$. Harmonic progression (HP) is a mathematical sequence formed from the reciprocals of the terms in an AP sequence.
Complete step-by-step answer:
We know that the standard quadratic equation is given by $a{{x}^{2}}+bx+c=0$ where $a,b,c$ are real numbers with condition has equal roots when the discriminant $D$ satisfies the condition $D={{b}^{2}}-4ac=0$
We are given from the question three expressions of $P,Q,R$ respectively as
\[\begin{align}
& P={{a}^{2}}b+a{{b}^{2}}-{{a}^{2}}c-a{{c}^{2}} \\
& Q={{b}^{2}}c+b{{c}^{2}}-{{a}^{2}}b-a{{b}^{2}} \\
& R={{c}^{2}}a+c{{a}^{2}}-{{c}^{2}}b-c{{b}^{2}} \\
\end{align}\]
We try to express $P,Q,R$ in cyclical form by taking ${{a}^{2}},a$ common in $P$, ${{b}^{2}},b$ common in $Q$ and ${{c}^{2}},c$ common in $R$. We have,
\[\begin{align}
& P={{a}^{2}}\left( b-c \right)+a\left( {{b}^{2}}-{{c}^{2}} \right)={{a}^{2}}\left( b-c \right)+a\left( b-c \right)\left( b+c \right)=a\left( b-c \right)\left( a+b+c \right) \\
& Q={{b}^{2}}\left( c-a \right)+b\left( {{c}^{2}}-{{a}^{2}} \right)={{b}^{2}}\left( c-a \right)+b\left( c-a \right)\left( c+a \right)=b\left( c-a \right)\left( a+b+c \right) \\
& R={{c}^{2}}\left( a-b \right)+c\left( {{a}^{2}}-{{b}^{2}} \right)={{c}^{2}}\left( a-b \right)+c\left( a-b \right)\left( a+b \right)=c\left( a-b \right)\left( a+b+c \right) \\
\end{align}\]
We are further given in the question that $a,b,c$ are all positive real numbers and the equation $P{{x}^{2}}+Qx+R=0$ has equal roots. We can put the value of $P,Q,R$ in the given quadratic equation $P{{x}^{2}}+Qx+R=0$ and have,
\[\Rightarrow a\left( b-c \right)\left( a+b+c \right){{x}^{2}}+b\left( c-a \right)\left( a+b+c \right)x+c\left( a-b \right)\left( a+b+c \right)=0\]
Since $a,b,c$ are positive real numbers $a+b+c$ cannot be zero and we can divide $a+b+c$ in both side of the above equation to have,
\[\Rightarrow a\left( b-c \right){{x}^{2}}+b\left( c-a \right)x+c\left( a-b \right)=0\]
The discriminant of the above quadratic equation is zero since the quadratic equation has equal roots. So we have
\[\begin{align}
& {{\left( b\left( c-a \right) \right)}^{2}}-4\times a\left( b-c \right)\times c\times \left( a-b \right)=0 \\
& \Rightarrow {{b}^{2}}{{\left( c-a \right)}^{2}}-4ac\left( ab-{{b}^{2}}-ca+bc \right)=0 \\
& \Rightarrow {{b}^{2}}{{c}^{2}}+{{b}^{2}}{{a}^{2}}-2a{{b}^{2}}c-4{{a}^{2}}bc+4a{{b}^{2}}c+4{{a}^{2}}{{c}^{2}}-4ab{{c}^{2}}=0 \\
& \Rightarrow {{a}^{2}}{{b}^{2}}+{{b}^{2}}{{c}^{2}}+4{{a}^{2}}{{c}^{2}}+2a{{b}^{2}}c-4ab{{c}^{2}}-4{{a}^{2}}bc=0 \\
& \Rightarrow {{\left( ab \right)}^{2}}+{{\left( bc \right)}^{2}}+{{\left( -2ac \right)}^{2}}+2\times ab\times bc+2\times bc\times \left( -2ac \right)+2\times ab\times \left( -2ac \right)=0 \\
\end{align}\]
We use the algebraic identity ${{\left( x+y+z \right)}^{2}}={{x}^{2}}+{{y}^{2}}+{{z}^{2}}+2xy+2yz+2zx$ for $x=ab,y=bc,z=-2ac$ in the above step to have
\[\Rightarrow {{\left( ab+bc-2ac \right)}^{2}}=0\]
We take square root of both side of the above step to have,
\[\begin{align}
& \Rightarrow ab+bc-2ac=0 \\
& \Rightarrow ab+bc=2ac \\
\end{align}\]
Since $a,b,c$ are positive real numbers $abc$ cannot be zero and we can divide $abc$ in both side of the above equation to have,
\[\Rightarrow \dfrac{1}{a}+\dfrac{1}{c}=\dfrac{2}{b}\]
The above relation implies that $a,b,c$ are in HP. So the correct option C\[\]
So, the correct answer is “Option C”.
Note: We can alternatively solve using the product of roots of $P{{x}^{2}}+Qx+R=0$ and equating it to a constant. The key in this problem is to express the discriminant into a square of $\left( ab+bc-2ac \right)$. Harmonic progression (HP) is a mathematical sequence formed from the reciprocals of the terms in an AP sequence.
Recently Updated Pages
Master Class 11 English: Engaging Questions & Answers for Success
Master Class 11 Computer Science: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Economics: Engaging Questions & Answers for Success
Master Class 11 Business Studies: Engaging Questions & Answers for Success
Trending doubts
10 examples of friction in our daily life
What problem did Carter face when he reached the mummy class 11 english CBSE
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
The sequence of spore production in Puccinia wheat class 11 biology CBSE